Emergence of Drug Resistance in the Swiss HIV Cohort Study Under Potent Antiretroviral Therapy Is Observed in Socially Disadvantaged Patients. (7th March 2019) - Abela, Irene A; Scherrer, Alexandra U; Böni, Jürg; Yerly, Sabine; Klimkait, Thomas; Perreau, Matthieu; Hirsch, Hans H; Furrer, Hansjakob; Calmy, Alexandra; Schmid, Patrick; Cavassini, Matthias; Bernasconi, Enos; et al.
Abstract: Background: The rate of acquired human immunodeficiency virus type 1 (HIV-1) drug resistance (ADR) has fallen dramatically since introduction of combined antiretroviral therapy (cART) in Switzerland. However, clinical experience indicates that there are still patients at risk of newly acquiring drug resistance despite having access to cART. Here, we characterized risk factors for ADR, to improve patient care and prevent emergence of drug resistance and treatment failure. Methods: We performed a case-control study to identify risk factors for ADR in all patients starting their first cART in the Swiss HIV Cohort Study (SHCS) since 1996. The SHCS is highly representative and includes >75% of patients receiving ART in Switzerland. To this end, we implemented a systematic medical chart review to obtain more detailed information on additional parameters, which are not routinely collected in the SHCS. The collected data were analyzed using univariable and multivariable conditional logistic regression. Results: We included in our study 115 cases and 115 matched controls. Unemployment (multivariable odds ratio [mOR], 2.9 [95% confidence interval CI, 1.3–6.4]; P = .008), African origin (mOR, 3.0 [95% CI, 1.0–9.2]; P = .047), comedication with anti-infectives (mOR, 3.7 [95% CI, 1.0–12.6]; P = .045), and symptoms of mental illness (mOR, 2.6 [95% CI, 1.2–5.5]; P = .012) were associated with ADR in the multivariable model. Conclusions: Although ADR has become very rare with cART due to new potent therapies, patients in socially challenging life situations or presenting with mental health issues are at higher risk for drug resistance. Prompt identification and adequate support of these patients before ADR will prevent treatment failure and HIV-1 transmission. Abstract : In a case-control study, we were able to identify specific risk factors for acquired drug resistance in all patients starting their first combination antiretroviral therapy regimen in the Swiss HIV Cohort Study since 1996.